How much should we trust Regression-Kink-Design estimates? - Michihito Ando (Uppsala University, Department of Economics, 2013)
In a Regression Kink (RK) design with a finite sample, a confounding smooth nonlinear relationship between an assignment variable and an outcome variable around a threshold can be spuriously picked up as a kink and result in a biased estimate. In order to investigate how well RK designs handle such confounding nonlinearity, I firstly implement Monte Carlo simulations and then study the effect of fiscal equalization grants on local expenditure using a RK design. Results suggest that RK estimation with a confounding nonlinearity often suffers from bias or imprecision and estimates are credible only when relevant covariates are controlled for.
urn:nbn:se:uu:diva-211572
Keywords: C13; C21; H71; H72; H77; 330; Regression Kink Design; Endogenous regressors; Intergovernmental grants; Flypaper effect